Pengertian dan Syarat Mujtahid dalam Ilmu Fikih dan Perkembgannya Diri Masa Kemasa - Abdul Latif Khan; Muhamad Yusron; Maulana El Yunusi (STIKes Ibnu Sina Ajibarang, 2024)
This article discusses in depth the meaning and requirements of a mujtahid in the science of jurisprudence and its development from time to time in the Islamic context. A mujtahid is an Islamic legal expert who is able to carry out ijtihad, which is the process of drawing law from Islamic legal sources using certain interpretation methods. The requirements for becoming a mujtahid include expertise in Arabic, in-depth knowledge of the Koran, Hadith, and the principles of ushul fiqh. This article also reviews several famous mujtahid figures throughout Islamic history and their role in developing and forming the sharia legal system. Understanding the concepts of mujtahid and ijtihad is important in understanding the evolution of Islamic law from time to time.